Upaya Memperkokoh Landasan Filosofis Pendidikan Agama Islam - Abdul Haris Rasyidi (Tarbiyah Departement collaboration with AMCA, 2017)
This paper includes the study of philosophy of Islamic education that specifically aims to want to see more in the effort to strengthen the philosophical foundations of Islamic education in a scholarly framework described by Muhammad Jawwad Ridla namely ontology, epistemology, and axiology Islamic sciences. The approach used in this paper is a methodical approach. This approach is used to find and discover the nature of truth and the result is within their (relevant) with a view of the problems posed. On that basis, the conclusion in this paper is that there is some basic foundation that could serve as the basis for building understanding about the nature of education Islamo them are ogy knowledge of Islam, Islamic religious sciences epistemology, and axiology knowledge of Islam.